Pengaruh Massage Efflurage terhadap Intensitas Nyeri Persalinan dan Pembukaan Jalan Lahir Fase Aktif - Riris Sitorus; Nining Pelawati; Grace Erlyn D.S (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Massage effleurage is a touch or gentle, slow, long and unbroken stroke using the tips of the fingers. This massage effleurage aims to make mothers feel comfortable and relaxed, close the gate of pain and increase endorphin hormone production. This study aims to determine whether there is an effect of massage effleurage on labor pain intensity and opening of the first phase of the birth pathway in the active phase at the Pratama Nining Pelawati Clinic, Lubuk Pakam District. The research method used was quasi-experimental (Quasi Experiment) with one group pre-test and post-test design. The population in this study were all mothers in the first phase of primigravida, the sample in this study was 18 respondents with a sampling technique using accidental sampling in accordance with inclusion criteria. The results showed that by using the Paired Sample T-Test analysis of massage effleurage to reduce the intensity of labor pain where the p-value of 0.001 <α = 0.05, it can be concluded that there was an effect of giving massage effleurage on the intensity of the first stage of postgravida pain active phase. However, there is no effect of giving massage effleurage to the acceleration of opening of the birth canal.